Koenigicine, a Carbazole Alkaloid, Mitigates Type 2 Inflammation and Alleviates Asthma in Animal and Cell Models - Wang, Qing Hua; Ma, Ming Chao; Zhou, Ming Zhi; Wang, Xiao Yan (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Allergic asthma is a global epidemic that significantly impacts the quality of life for both adults and children. Inhaled corticosteroids are regarded as the primary treatment for asthma, effectively alleviating symptoms over the long term; however, they do not adequately address Type 2 inflammation, which can exacerbate the condition. Therefore, we sought to evaluate the efficacy of koenigicine, a carbazole alkaloid, in mitigating Type 2 inflammation using both an ovalbumin-sensitized animal model and an LPS-induced cell model. Materials and Methods: BALB/c mice were sensitized with Ovalbumin+AlOH3 and treated with koenigicine. Bronchoalveolar lavage fluid and pulmonary tissue were excised to examine koenigicine impact on Ova induced inflammation. Total and differential cell count, quantification of nitric oxide, myeloperoxidase activity, eotaxin and Ova specific IgE were performed to analyze efficacy of koenigicine against the inflammatory response induced due to Ovalbumin sensitization. Lipid peroxidation and the antioxidant levels were quantified to evaluate the antioxidant effect of koenigicine. To confirm the impact of koenigicine in mitigating Th2 inflammation the IL4, IL5, IL-13 and the immunomodulators TNF-α and INF-γ were quantified. Histopathological examination of pulmonary tissue was performed to further assess the koenigicine efficacy in asthmatic condition. Results: To evaluate the efficacy of koenigicine against the inflammatory response induced by ovalbumin sensitization, we conducted total and differential cell counts, measured nitric oxide levels, assessed myeloperoxidase activity and quantified eotaxin and ovalbumin-specific IgE. Additionally, lipid peroxidation and antioxidant levels were assessed to determine the antioxidant effects of koenigicine. We quantified interleukins IL-4, IL-5 and IL-13, along with the immunomodulators TNF-α and INF-γ, to confirm koenigicine's impact on mitigating Th2 inflammation. Furthermore, histopathological examination of pulmonary tissue was performed to further evaluate the effectiveness of koenigicine in an asthmatic context. The cytotoxicity of koenigicine was investigated in RAW264.7 macrophages with MTT assay. Koenigicine pretreated RAW264.7 macrophages were exposed to LPS stimulation and assessed for inflammatory response. Conclusion: Koenigicine treatment demonstrated a significant and effective response in both the animal and cell models. Our analysis confirms that koenigicine is a safe and potent antioxidant that effectively reduces Th2 inflammation and alleviates allergic asthma.
Keywords: Allergic Asthma; Anti-asthmatic drug; LPS stimulation; Ovalbumin sensitization; Type; 2 inflammation; Koenigicine